Evaluación de métodos de derivatización de fosfolípidos y dimicocerosatos de ftiocerol asociados al Mycobacterium tuberculosis (2017)
"The study of resistance to drugs by a mycobacterium can be developed by means of compounds characteristic of this biological system, since from these compounds can be considered a potential biomarker that allows the detection or monitoring of a disease. In the case of tuberculosis and Mycobacterium tuberculosis, lipids are part of these compounds, because of they are fundamental components of biological membranes and exert many important functions... Taking into account previous description, the work developed was based on the study of the lipids of three strains: control, susceptible and resistant to rifampicin; by gas chromatography and liquid chromatography, coupled to mass spectrometry, and thus, from the results found to be able to analyze the differences in the chromatographic profiles of the lipids of interest." -- Tomado del Formato de Documento de Grado.